Encouraging Mothers for Routine Pediatric Dental Check-Up Through Cadres Empowerment Program - Setijanto, R. Darmawan; Rachmawati, Rita Yuana; Kandar, Hayyin Sabila; Hartono, Dwicha Rahma Nuriska; Novitananda, Agtadila; Laksono, Revian Gigih; Thalia, Audina; Dias, Dennaya Listya; Adityasari, Rachma; Sativa, Naura Athiyyah; Fauzi, Ahmad (Indonesian Journal of Dental Medicine, 2019)
Background: Oral and dental hygiene is essential for physical health and well-being, and it can affect speech, mastication, and self-confidence. Children under five are not able to brush their teeth independently, do not have manual dexterity and psychological maturity to understand the importance of maintaining oral health. Therefore, parental role, especially maternal role, is critical in maintaining children's dental and oral health. An epidemiological study under Kalijudan Public Health Center coverage revealed that maternal parenting style significantly affected dental and oral health care in children per caries severity index using def-t. A promotional program was needed to strengthen the maternal perceived control domain to promote dental and oral health in children. The "SEKOLAH KADER” program was intended to train health cadres in disseminating dental health information and assisting mothers in child dental and oral health care. Purpose: To increase cadres' knowledge levels about pediatric dental and oral care through "SEKOLAH KADER.” Upon program completion, the cadres were expected to help to disseminate dental health information and assisting mothers in terms of child dental and oral health. Methods: The program involved 6 cadres from 3 local Integrated Health Centre. The program material was distributed in hard and soft copies. Results: The paired t-test showed a significance value of 0.018 (p <0.05). This indicates that there was a significant increase from pre-test to post-test evaluation results. Conclusion: This program has succeeded in increasing cadres' knowledge levels about basic dental health care.